If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + -8 + 2(h + -8) = 72 Reorder the terms: h + -8 + 2(-8 + h) = 72 h + -8 + (-8 * 2 + h * 2) = 72 h + -8 + (-16 + 2h) = 72 Reorder the terms: -8 + -16 + h + 2h = 72 Combine like terms: -8 + -16 = -24 -24 + h + 2h = 72 Combine like terms: h + 2h = 3h -24 + 3h = 72 Solving -24 + 3h = 72 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 3h = 72 + 24 Combine like terms: -24 + 24 = 0 0 + 3h = 72 + 24 3h = 72 + 24 Combine like terms: 72 + 24 = 96 3h = 96 Divide each side by '3'. h = 32 Simplifying h = 32
| 47=19-4x | | 39+x=30+2x | | R-20+4=18 | | 1521=39p+390 | | M+52=53 | | 14y+6(4-8y)= | | y-1/3x=0 | | D-35=50 | | 10(0.6x+4)=10(0.3x+7) | | 2x/(x-3)=8 | | 1521=39(p+10) | | A-3=24 | | 10=17+b | | 3v+12=63 | | X-100=-10 | | p^6/p^4= | | 28=17-r | | Y-150=15 | | -3x-9+7x+27=11x+9-2x | | 33=20+k | | A-15=25 | | 3080=44(p+25) | | 4/3y-8=24 | | 930=5(x+17) | | -m-28=-4(2-m) | | 6+2ln(4x)=12 | | 3x^2-30=4 | | 3(11/2-1/8) | | 203=7(8-7x) | | 1/3x-9=3 | | 1/3x-9=3 | | 5+2m+6=3 |